The Stapled Peptide PM2 Stabilizes p53 Levels and Radiosensitizes Wild-Type p53 Cancer Cells - Mortensen, Anja Charlotte Lundgren; Spiegelberg, Diana; Brown, Christopher John; Lane, David Philip; Nestor, Marika (Frontiers in Oncology, 2019)
The tumor suppressor p53 is a key mediator of cellular stress and DNA damage response cascades and is activated after exposure to ionizing radiation. Amplifying wild-type p53 expression by targeting negative regulators such as HDM2 in combination with external beam radiotherapy (EBRT) may result in increased therapeutic effects. The novel stapled peptide PM2 prevents HDM2 from suppressing wild-type p53, and is thus a promising agent for therapeutic combination with EBRT. Effects of PM2 and potential PM2-induced radiosensitivity were assessed in a panel of cancer cell lines using 2D cell viability assays. Western Blot and flow cytometric analyses were used to investigate the mechanisms behind the observed effects in samples treated with PM2 and EBRT. Finally, PM2-treatment combined with EBRT was evaluated in an in vitro 3D spheroid model. PM2-therapy decreased cell viability in wild-type p53, HPV-negative cell lines. Western Blotting and flow cytometry confirmed upregulation of p53, as well as initiation of p53-mediated apoptosis measured by increased cleaved caspase-3 and Noxa activity. Furthermore, 3D in vitro tumor spheroid experiments confirmed the superior effects of the combination, as the only treatment regime resulting in growth inhibition and complete spheroid disintegration. PM2 induces antitumorigenic effects in wt p53 HPV-negative cancer cells and potentiates the effects of EBRT, ultimately resulting in tumor eradication in a 3D spheroid model. PM2 shows great potential as a new wt p53 specific tumor-targeting compound, and the combination of PM2 and EBRT could be a promising strategy to increase therapeutic effects and decrease adverse effects from radiotherapy.